Caracterização biométrica e química da folha de Mentha pulegium x spicata (Lamiaceae) - Martins, M. B G [UNESP]; Martins, A. R. [UNESP]; Cavalheiro, Alberto José [UNESP]; Telascrêa, M. [UNESP] (My University, 2004)
The hybrid Mentha pulegium x spicata, also well-known as poejo de praia, it is a perennial, low plant, with fields, violet stem and opposite leaves, with lance format and sawed board, presenting characteristic smell. The objective of the present work was accomplish a study of the leaf anatomy, including a biometric study of tissue and quantitative analysis of secretory trichomes/mm2 and of stomata/mm2 in both faces of the epidermis, besides a chemical analysis of the essential oil. Histological permanent laminas were made for anatomical analysis of the leaf surface and also sheets of the impression to foliate for the count of the trichomes number and stomatas. The chemical studies were made through the extraction of the essential oil by hydrodistillation and analyzed in GC-MS. The capitate and peltates trichomes are present on both sides of the leaf, even so they prevail in the abaxial surface. The variance analysis show that there are significant differences for the number of capitate trichomes and tectores between the adaxial and abaxial surfaces, but they are not significant for the peltate trichoma. The analyzed of essential oil shows the presence of a majority component, trans piperitone epoxide, being it responsible for more than 80% of the relative composition in the essential oil.
Biometric and chemical characterization of Mentha pulegium x spicata (Lamiaceae) leaves
Keywords: Biometry; CG-MS; Essential oil; Mentha pulegium x spicata; Plant anatomy; Trichome; essential oil; mentha pulegium spicata extract; plant extract; unclassified drug; biometry; gas chromatography; mass spectrometry; medicinal plant; mentha pulegium spicata; plant leaf; quantitative analysis; surface property